Slovak Republic : Living Standards, Employment, and Labor Market Study - World Bank (Washington, DC, 2013)
By most indicators the Slovak Republic has achieved a high level of human and social development. Despite the country's generally high living standards and overall level of development, there are families in Slovakia whose living conditions are below what is considered to be socially acceptable. By societal standards, these families and individuals are poor. The objective of this study is to analyze this poverty, so as to help design measures and policies to reduce it. The study also seeks to understand the phenomenon of unemployment--the main cause of poverty--and propose actions to alleviate it. The report is organized as follows: After Chapter 1, which explains the background of poverty and inequality in the Slovak Republic, Chapter 2 addresses the challenge of generating employment, including rising unemployment and inactivity, job reallocation during transition, the importance of the regional and skills mismatch, and conclusions and policy recommendations that enhance employment creation. Chapter 3 explores the role of the safety net system, particularly unemployment insurance and other forms of social assistance; presents a brief simulation analysis of the disincentives provided by unemployment insurance, social assistance, and social support; provides an empirical analysis of disincentive effects; and ends with a discussion of the policy implications. Chapter 4 focuses on the poverty and welfare of the Roma population. Finally Chapter 5 telescopes regional disparities.